Taxation and private investment: evidence for Kenya - Njuru, Stephen Gitahi; Ombuki, Charles; Wawire, Nelson; Okeri, Susan (My University, 2013)
Private investment in Kenya has been low for the last four decades. This has stimulated much concern to the policy makers’ bearing in mind that investment is a key variable influencing economic growth. Several economic policies have been designed with an aim of rejuvenating private investment which was robust during the first decade of independence before deteriorating in the other decades. The main purpose of this study was to investigate the impact of taxation on private investment in Kenya. Vector auto-regression technique was used to achieve study objectives. Time series research design was used covering period 1964-2010. The study found that VAT, income tax and establishment of Kenya Revenue Authority (KRA) had negative impact on private investment while excise tax, import tax and tax amnesty impacted positively on private investment. The study concludes appropriate tax system and progressive tax reforms are necessary to ensure that private investors are given enabling environment to establish.\